2023
DOI: 10.1002/smll.202300413
|View full text |Cite
|
Sign up to set email alerts
|

A Paradigm Shift from 2D to 3D: Surface Supramolecular Assemblies and Their Electronic Properties Explored by Scanning Tunneling Microscopy and Spectroscopy

Abstract: Exploring supramolecular architectures at surfaces plays an increasingly important role in contemporary science, especially for molecular electronics. A paradigm of research interest in this context is shifting from 2D to 3D that is expanding from monolayer, bilayers, to multilayers. Taking advantage of its high‐resolution insight into monolayers and a few layers, scanning tunneling microscopy/spectroscopy (STM/STS) turns out a powerful tool for analyzing such thin films on a solid surface. This review summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 176 publications
0
4
0
Order By: Relevance
“…In these fundamental building blocks, the manipulation and study of molecules in 3D space through advanced self‐assembly methods, such as supramolecular chemistry and host–guest processes, can significantly contribute to the advancement of multidimensional and multifunctional nanostructures and biomaterials. [ 13–24 ] These interactions used for molecular self‐assembly are inherently short‐range ordering and relatively weak, posing challenges in assembling them into programmable, long‐range ordered structures with high degree of freedom and applying them to various functional devices, such as soft actuators, proton transport membranes, and high‐strength materials. [ 25–28 ] To address this issue, directional assembly methods [ 29 ] such as the template method, [ 30–35 ] solution evaporation, [ 36 ] and shear flow field [ 37–40 ] have all been employed to assemble small molecules into ordered structures.…”
Section: Introductionmentioning
confidence: 99%
“…In these fundamental building blocks, the manipulation and study of molecules in 3D space through advanced self‐assembly methods, such as supramolecular chemistry and host–guest processes, can significantly contribute to the advancement of multidimensional and multifunctional nanostructures and biomaterials. [ 13–24 ] These interactions used for molecular self‐assembly are inherently short‐range ordering and relatively weak, posing challenges in assembling them into programmable, long‐range ordered structures with high degree of freedom and applying them to various functional devices, such as soft actuators, proton transport membranes, and high‐strength materials. [ 25–28 ] To address this issue, directional assembly methods [ 29 ] such as the template method, [ 30–35 ] solution evaporation, [ 36 ] and shear flow field [ 37–40 ] have all been employed to assemble small molecules into ordered structures.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional (2D) self-assembled molecular networks (SAMNs) of organic molecules on atomically flat, and often conductive, surfaces have been studied extensively over the past decades due to their potential applicability in different areas ranging from organic photonic or electronic devices to single-molecule switches. In these reports, it has been demonstrated that during their formation, the surface interacts with molecules and acts as a template facilitating the formation of highly ordered supramolecular networks. Combined with other noncovalent intermolecular forces, such as hydrogen bonding, , van der Waals (vdW), electrostatic, dipolar, , and π–π interactions, , molecular assemblies with complex architectures have been built.…”
Section: Introductionmentioning
confidence: 99%
“…5 Most previous reports described the epitaxial growth of the same molecular component. 5,6 Those featuring a different component on the first SAMN layer are limited, 7,8 particularly at the liquid/solid interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Self-assembled molecular networks (SAMNs) formed by organic molecules on solid surfaces are not only the subject of curiosity driven interest but may have also interesting applications. One recent challenge is the construction of three-dimensional (3D) architectures through the epitaxial structural growth from surface-confined SAMNs, not only from a crystal engineering viewpoint but also for the fabrication of functional materials such as 3D metal–organic frameworks and molecular devices . Most previous reports described the epitaxial growth of the same molecular component. , Those featuring a different component on the first SAMN layer are limited, , particularly at the liquid/solid interface.…”
Section: Introductionmentioning
confidence: 99%